Manila mango dieback disease: histological characterization and occurrence in the central area of Veracruz - Noa-Carrazana, Juan Carlos; Córdova-Nieto, Clara; Saucedo-Picazo, Liliana Eunice (Revista Mexicana de Ciencias Agrícolas, 2025)
Dieback is one of the diseases that generates the greatest impact on mango, it affects the entire structure of the tree, leading it to cause losses in production. This research studied the impact of the disease in five localities in the central area of the state of Veracruz from 2016 to 2017 and carried out a histological characterization of the damage caused by Lasiodiplodia pseudotheobromae in Manila mango. The results revealed an incidence ranging from 38% to 80%, a severity ranging from 1.5 to 2.59 degrees, and a high disease index of 0.58 to 2. Histologically, the fungus affected various plant tissues, mainly the vascular cambium, so the inner and outer bark was affected, causing the destruction of the xylem and phloem vessels as well as the production of gum. This pathogenic activity could result in damage to the phloem, preventing the transport of nutrients and mineral salts, and damage to the xylem, preventing the passage of water, which would eventually trigger the death of the plant. Knowing how the pathogenic fungus acts places us in the opportunity for early intervention for the management of the disease.